USAHA PENGOLAHAN IKAN TAWES PRESTO DI PESISIR WADUK GAJAH MUNGKUR KABUPATEN WONOGIRI - Eri Yusnita Arvianti; Pandoyo Pandoyo (Universitas Tribhuwana Tunggadewi, 2008)
A study that was aimed to describe the effects of capital, selling price and labour cost on income from presto tawes fish processing business at area of Gajah Mungkur Reservoir, Wonogiri Regency was conducted at Wonogiri and Wuryantoro Districts. Thirty farmers out of 42 farmers dealing with such a business were used as respondents. Results of this study showed that capital, selling price and labour cost either simultaneously or partially affected income. Capital was the most dominant variable affecting income of presto tawes fish processing business